CONSTRUCTION OF NURSING CULTURE IN THE CONDITIONS OF SOVIET IDEOLOGY: ESTONIAN EXAMPLE - Talvik, Merle; Tulva, Taimi; Ernits, Ülle; Puusepp, Kristi (PROFESSIONAL STUDIES: Theory And Practice, 2022)
The aim of the study is to analyse the development of nursing culture in the Estonian Soviet Socialist Republic. The analysis of scientific literature and empirical material (interviews) was conducted in 2019 and 2021. During Soviet era nursing was strongly influenced by ideology. The goal of civil protection was considered important. The nurses’ daily work was characterised by poor working conditions, hierarchical employment relationship and miserable career prospects. The last decade of the Soviet period encountered the release of limits initiated by the ideas of perestroika and glasnost. Keywords: Estonian SSR, nursing culture, Soviet ideology, propagandistic orientation, activity patterns of nurses.